Love me do : the Beatles' progress - Braun, Michael, 1936- (Harmondsworth, Middlesex, Eng. : Penguin Books, 1964)
A behind-the-scenes look at the Beatles' first British tour in 1963, as well as their historic live appearance at the Royal Variety Performace at the London Palladium.
'Penguin books 2278'--Front endpaper
Koleksi Sumbangan : Dr. Syed Husin Ali.
Keywords: Beatles; Rock groups -- England -- History; Popular music -- England -- History and criticism; Rock music -- England -- History and criticism